1979
DOI: 10.1111/j.1442-9993.1979.tb01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Food of the platypus (Ornithorhynchus anatinus) with notes on the food of brown trout (Salmo trutta) in the Shoalhaven River, N.S.W.

Abstract: Feeding in the platypus (Ornithorhynchus anatinus) was investigated by identifying material found in the cheek pouches of animals trapped in nets in a study area on the upper Shoalhaven River, N.S.W. Benthic samples were taken in the rapids and pools of the river and the relative abundance of food items available was related to the food found in the platypus cheek pouches. The main food organisms found were insect larvae, notably Trichoptera, Diptera, Coleoptera, Ephemeroptera and Odonata. Subsidiary food item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 10 publications
(11 reference statements)
1
38
1
Order By: Relevance
“…The captive individuals in this study also showed marked diving bradycardia, an ability to inspire a large quantity of air prior to diving and the capacity for dives longer than those recorded in ¢eld observations (Evans et al 1994). Kruuk (1993) used a ratio of time under water to time on the surface as a measure of foraging e¤ciency in the platypus, which normally needs to collect several small food items during each dive, rather than single large prey items (Faragher et al 1979;Grant 1982). He indicated that foraging e¤ciency was increased in eutrophic waters, owing to a presumed high abundance of benthic invertebrates, but also found that the distances covered during foraging dives were greater in his eutrophic sites than in the more oligotrophic ones.…”
Section: Food and Foraging Activitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The captive individuals in this study also showed marked diving bradycardia, an ability to inspire a large quantity of air prior to diving and the capacity for dives longer than those recorded in ¢eld observations (Evans et al 1994). Kruuk (1993) used a ratio of time under water to time on the surface as a measure of foraging e¤ciency in the platypus, which normally needs to collect several small food items during each dive, rather than single large prey items (Faragher et al 1979;Grant 1982). He indicated that foraging e¤ciency was increased in eutrophic waters, owing to a presumed high abundance of benthic invertebrates, but also found that the distances covered during foraging dives were greater in his eutrophic sites than in the more oligotrophic ones.…”
Section: Food and Foraging Activitiesmentioning
confidence: 99%
“…Food items are stored in these pouches during foraging but are then masticated and ¢nely ground by the time they are ingested, so that the majority of material in the digestive system is not recognizable. The presence of benthic invertebrate species, especially insect larvae, in the cheek pouches have been noted by most investigators (Bennett 1835;Crowther 1879;Allport 1878;Semon 1899;Burrell 1927;Fleay 1944;Faragher et al 1979;Grant 1982), although free-swimming species, such as shrimps (Crowther 1879;Fleay 1944;Faragher et al 1979), cray¢sh (Burrell 1927;Fleay 1944Fleay , 1980, beetles (Crowther 1879), water bugs (Burrell 1927), and tadpoles (Fleay 1944), also appear to be included in the diet. After watching a platypus foraging in the gravel bottom of a stream in Tasmania during the spawning season of the grayling, Allport (1878) indicated that the species may take ¢sh eggs and indicated that he could not`conscientiously recommend the owners of trout streams to encourage the presence of Ornithorhynchus anatinus'.…”
Section: Food and Foraging Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Insectivorous bird activity was also closely related to variations in insect emergence ([50% of the biomass was chironomids) from a prairie stream in Kansas (Gray 1993). Some Australian studies (Faragher et al 1979;Ingram and De Silva 2007) also reinforce the importance of chironomids as a source of food for other species. Faragher et al (1979) reported that chironomids and other dipterans were among the most important food sources for platypus and brown trout in the Shoalhaven River (NSW).…”
Section: Discussionmentioning
confidence: 69%